HUBUNGAN UMUR DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI DESA SLUKATAN MOJOTENGAH - romdiyah; Resmi, Dewi Candra; Istiqomah, Titi (Maternity and Neonatal : Jurnal Kebidanan, 2023)
Pregnancy is a period that married couples look forward to. During pregnancy, physical and psychological changes will occur. The need for iron increases and iron intake is low during pregnancy. Anemia can occur in pregnancies when the mother is under 20 years and over 35 years. Pregnant women are advised to carry out HB checks so that anemia can be prevented. Objective: to find out whether maternal age is related to anemia. Research method: The research design uses a correlation design with a cross sectional approach. The population in this study who made ANC visits at PKD Slukatan were 127 pregnant women. The samples taken in the research were 79 pregnant women using the Accidental Sampling technique. Research results: the majority of respondents were of reproductive age (20-35 years). The status of respondents who experienced anemia was 57%. The results of the chi square test analysis obtained p = 0.001 (p < 0.005), meaning that there is a relationship between age and the incidence of anemia in mothers.